Irradiated polyethylene terephthalate and fly ash based grouts for semi-flexible pavement: design and optimisation using response surface methodology - Khan, M.I. (Taylor and Francis Ltd., 2020)
This study explores the effectiveness of using recycled irradiated waste polyethylene terephthalate (PET) as a partial replacement for cement in the formulation of cementitious grouts. This study investigates the impact of regular and irradiated PET and fly ash (FA) on the flowability, drying shrinkage, compressive strength and flexural strength of cementitious grouts. It was observed that partial replacement of cement with normal PET (in the range of 5â10 by mass of cement) resulted in a reduction (between 26 and 46) in compressive strength of the cured grout. Interestingly, the use of irradiated PET instead of regular PET restores 8â22 of the compressive strength. Additionally, response surface methodology (RSM) is used to design the experiments, analyze the responses, and optimise the independent variables. A high R 2 and adequate precision of the ANOVA is an indication of a good agreement between the factors and responses. Besides, gamma irradiation makes it possible to use a higher percentage of 2.57â4.75 waste PET as cement replacement while retaining the target flow and strength properties. Therefore, the proposed treatment of PET with gamma radiation could be an effective way for recycling waste PET and a significant step towards achieving the zero-waste challenge. Â© 2020 Informa UK Limited, trading as Taylor & Francis Group.